Academic corruption among nigerian students: the roles of contextual and personal factors (2019)
The Contemporary educational environment is flocked with cheating, plagiarism, unauthorized collaboration, purchased essays and term papers, shred test and quiz files, and identity spoofing for online and departmental examinations, to undermine commonly understood, long-standing educational ideals in Nigerian institutions. This motivated the need to investigate the roles contextual and personal factors play in academic corruption among Nigerian students. A correlational design was adopted with a sample of 250 undergraduates randomly selected from five faculties of the University of Ibadan. Data were collected using three measuring scales, Institutional Integrity Policy Scale, a=0.752, Peer culture, a= 0.731 and Academic Corruption scale; a=. 702). Three research questions were stated and tested at 0.05 level of significance using Pearson’s product moment correlation (PPMC) and multiple linear regression. It was discovered that there was a significant relationship between academic corruption and institutional integrity policy (r= 0.530, p<0.01) peer culture (r- 0.458, p<0.05) and age (r= 0.210, p<0.05) and gender (r= 0.101, p<0.05). The regression model showed institutional integrity policy (Beta = .750, t- 14.011, P<0.01) as the highest predictor of academic corruption followed by peer culture (Beta = -.467, t= -9.475, P<0.01), gender (Beta = .111, t= 1.877, P<0.05), but not with age (Beta = .008, t = 0.327, P>0.05). Among others, it was recommended that university administrators and faculty staff should rise to their responsibilities to ensure that students adhere to the ethics of academic integrity through an enforcement policy. The university counselling unit and the disciplinary committee should ensure that a corruption free culture is instilled in students through adequate disciplinary measures. Sincerity and integrity should also be rewarded.